HUKUM JUAL BELI TANPA IZIN EDAR PRODUK MINUMANN MORINGA CHEONG DI KOTA BANDA ACEH MENURUT HUKUM ISLAM - Zahiddin, Hendra Syaudayan (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2022)
Every human being, male or female, will not be separated from the practice of buying and selling, whether on a large or small scale, at the individual, community and even inter-country levels. Likewise, when someone wants to run a business, they should pay attention to the licensing of the product so that people who buy it will be more confident and safe and legal under the law. Moringa Cheong's product is a herbal drink made from fermented Moringa leaves, but it is immediately marketed even though the distribution permit has not been fully issued, so this is a problem in decision Number 341/Pid.Sus/2022/Pn.Bna. This research aims to find out what type of contract is used by shops and supermarkets with PT.Korea Aceh Mandiri in buying and selling food products in the form of Moringa Cheong drinks and to find out the judge's considerations in handing down sentences to Lee Chungyoung as the owner of PT.Korea Aceh Mandiri based on decision Number 341/Pid.Sus/2022/Pn BNA. Using Normative Jurisprudence as a research method, library research to obtain materials. The marketing process for the Moringa Cheong herbal drink uses a deposit agreement or wadi, ah, where the drink product is entrusted to supermarkets and drug stores in Banda Aceh City. When the product sells, the profits will be given according to what was agreed at the beginning. In decision Number 341/Pid.Sus/2022/Pn Bna, the judge considered that the defendant's good intentions in producing the Moringa Cheong drink product were to make the people who drank it healthy, and also that the distribution permit for the product was almost ready. throughout the process, but because of the defendant's lack of patience, what he didn't want happened.